Determinantes físicos e ecológicos que afetam as assembleias de aves no sudeste da Amazônia: o papel da história na distribuição das espécies - Maximiano, Marina (2019)
Amazonian rivers have been proposed to act as geographic barriers to species dispersal, either driving allopatric speciation or defining current distribution limits. The strength of the barrier varies according to the species ecological characteristics and the river physical properties. Environmental heterogeneity may also drive compositional changes, but have hardly been assessed in Amazonia. Aiming to understand the contributions of riverine barriers and environmental heterogeneity in shaping compositional changes in Amazonian forest bird assemblages, we focus on the Tapajós River. We investigate how spatial variation in species composition is related to physical barriers (Tapajós and Jamanxim rivers), ecological characteristics of the species (distinct guilds) and environmental heterogeneity (canopy reflectance, soils and elevation). We sampled birds through point counts and mist nets on both sides of the Tapajós and Jamanxim rivers. To test for relationships between bird composition and environmental data, we used Mantel and partial Mantel tests, NMDS and ANOVA + Tukey HSD. The Mantel tests showed that the clearest compositional changes occurred across the Tapajós River, which seems to act unequally as a significant barrier to the bird guilds. The Jamanxim River was not associated with differences in bird communities. Our results reinforce that the Tapajós River is a biogeographical boundary for birds, but environmental heterogeneity determines compositional variation within interfluves. These results contrast with diversity patterns described for other vertebrates, suggesting that upland forest birds singularly respond to large rivers as barriers in Amazonia, leading to erroneous extrapolations for interpreting biogeographic results for other Amazonian organisms.